HUBUNGAN PEMBELAJARAN GEOGRAFI TERHADAP PERSEPSI SISWA TENTANG MITIGASI BENCANA GEMPA BUMI DI SMA NEGERI 9 PADANG - David Syahdan; Syafri Amwar (STKIP Subang, 2026)
This research is motivated by the geographical conditions of Padang City, which is located in an earthquake-prone zone, thus requiring strong disaster preparedness within the school environment. The main objective of this study is to empirically analyze and test the influence of geography learning on students' perceptions of earthquake disaster mitigation at SMA Negeri 9 Padang. The method used in this research is a quantitative approach with a causal correlational type through a survey method. The final sample of this study consisted of 54 students from grades XI and XII. Data collection was carried out using a Likert-scale questionnaire instrument that had been tested for validity and reliability. The data analysis techniques applied included descriptive statistics and inferential analysis using a simple linear regression test to examine the hypothesis. The results showed that the implementation of geography learning was in the high category with an achievement percentage of 76.6%, which is in line with students' perceptions of disaster mitigation that were also in the high category with a percentage of 76.8%. The results of the simple linear regression test yielded an R value of 0.685, indicating a strong relationship, and an R Square value of 0.469. It can be concluded that there is a positive and significant influence of geography learning, which contributes 46.9% to the formation of students' perceptions of earthquake disaster mitigation at SMA Negeri 9 Padang, while the remaining percentage is influenced by other factors.